Peran Kegiatan MGMP dalam Meningkatkan Kreativitas Guru dalam Merancang Modul Ajar Berbasis Deep Learning di MAN 1 Sula - Adam, Adiyana; Limatahu, Kartini; Juliadharma, Minggusta; Buamona, Nurmala; Fitrianto, Arif Rahman (Peneliti.net, 2025)
This study explores the role of the Teacher Subject Forum (Musyawarah Guru Mata Pelajaran/MGMP) in enhancing teachers’ creativity in designing deep learning-based teaching modules at MAN 1 Sula. Using a qualitative descriptive approach, the research involved 15 teachers who actively participated in MGMP activities. Data were collected through interviews, observations, and documentation, and analyzed using an interactive model of data reduction, display, and conclusion drawing. The findings reveal that all participants successfully developed teaching modules aligned with the 2025 Merdeka Curriculum learning outcomes, emphasizing critical thinking, collaboration, creativity, and communication. The MGMP sessions, consisting of material delivery, practice, and evaluation, effectively fostered innovation, reflective practices, and professional collaboration among teachers. Despite challenges such as limited digital infrastructure and varying levels of digital literacy, MGMP proved to be a relevant and effective platform for supporting curriculum implementation and improving the quality of deep learning in the classroom.